Konstruksi Realitas Sosial dalam Praktik Green Accounting: Pendekatan Kualitatif terhadap Kesadaran Lingkungan Organisasi - Fadillah Fadillah; Romansyah Sahabuddin; Anwar Ramli; Ikhwan Maulana (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2025)
This study aims to understand how green accounting practices are constructed as a social reality within organizations and how environmental awareness develops through social interaction, organizational values, and culture. The research adopts an interpretive qualitative approach within the social construction paradigm (Berger & Luckmann, 1966). Data were collected through in-depth interviews, participant observation, and document analysis in organizations that have implemented sustainability reporting. The analysis employed an interpretive thematic approach to uncover the meanings underlying environmental accounting practices. The findings indicate that green accounting functions not only as a technical reporting instrument but also as a mechanism for shaping organizational moral and ecological awareness. Environmental awareness is constructed through three main stages: the externalization of sustainability values by leadership, objectivation through policies and reporting systems, and internalization within work behavior and organizational culture. Participatory, reflective, and innovation-oriented organizational cultures strengthen the substantive implementation of green accounting, whereas bureaucratic structures tend to produce symbolic practices or greenwashing. Theoretically, this study reinforces the view that accounting is a social practice that both shapes and is shaped by collective consciousness (Hopwood, 1992; Gray, 2010). Practically, the findings highlight the importance of visionary leadership and social learning spaces in fostering a sustainability-oriented organizational culture. Thus, green accounting is understood as a social process that plays a strategic role in realizing ethical, sustainable, and environmentally responsible organizations.